The isolation of fungi from lichens of the Magadan region and biological activity of their extracts - Suleimen, Ye.M.; Zheludeva, E.V.; Bazarkhankyzy, A.; Tekebayeva, Zh.B.; Buddha Bahadur Basnet; Nayekova, S.K.; Sarmurzina, Z.S. (KU Publ., 2021)
The study aims to isolate fungi from lichens of the Magadan region (Russia) and evaluate their antibacterial and antifungal activity. Fourteen species of lichen from the Magadan region (Russia) were selected for the study. Antibacterial activity was determined based on gram-positive (Staphylococcus aureus) and gramnegative bacteria (Escherichia coli). Antifungal activity was identified by using strains of Aspergillus terreus and Candida albicans. According to the results of the study, fungi isolated from lichens Peltigera leucophlebia (CD), Hypogymnia sachalinensis (CD) showed antifungal activity, and fungi from Peltigera leucophlebia (CD), Peltigera aphthosa (CD), Melanohalea olivacea (PDA, CD), displayed antibacterial activity. As a result of studying the biological activity, the fungi isolated from the lichen Peltigera leucophlebia (CD) have both antibacterial and antifungal activity.
Магадан облысы қыналарынан саңырауқұлақтардың алынуы және олардың ферментативті сығындыларының биологиялық белсенділігі
Выделение грибов из лишайников Магаданской области и биологическая активность их ферментативных экстрактов
Keywords: lichens; Magadan region; fungi; antibacterial activity; antifungal activity